В память о тебе: роман / Д. Калотай; пер. с англ. О. Буйвола - Калотай Дафна (Клуб семейного досуга, 2011)
Экземпляры: аб. ЦБ (20230621) / Инвентарный номер: 17127 / Цена: / Авт.знак: К17 / ББК: 84(7США)